Dual-channel coordination based on different power structure and pricing strategies. (28th December 2020) - Liu, Weihua; Wu, Wenfei; Yan, Xiaoyu; Wei, Wanying; Liu, Xinyun
With the rapid development of e-commerce, retailers have opened up online and offline dual channels for product distribution. This paper considers three pricing scenarios: 1) decentralisation; 2) concentration of power plus unified pricing; 3) concentration of power plus discrimination pricing and mainly obtains the following three conclusions.